A review of the subgenus Euprepiosaurus of Varanus (Squamata: Varanidae): morphological and molecular phylogeny, distribution and zoogeography, with an identification key for the members of the V. indicus and the V. prasinus species groups - Ziegler, Thomas; Schmitz, Andreas; Koch, André; Böhme, Wolfgang (Zootaxa, 2007)
We provide a synopsis of the currently recognized taxa within the subgenus Euprepiosaurus of Varanus, consisting of the V. indicus species group (in chronological order, V. indicus, V. doreanus, V. jobiensis, V. finschi, V. melinus, V. yuwonoi, V. caerulivirens, V. cerambonensis, V. juxtindicus, V. zugorum) and the V. prasinus species group (accordingly, V. prasinus, V. beccarii, V. kordensis, V. bogerti, V. keithhornei, V. telenesetes, V. macraei, V. boehmei, V. reisingeri). We summarize the taxonomic history of the species groups and highlight the morphology and distribution of the species in detail. Molecular genetic analyses confirm Euprepiosaurus and also the two contained species groups as monophyla. Our molecular (mitochondrial 16S rRNA gene) data further reinforce that V. beccarii, V. boehmei, V. keithhornei, and V. macraei are distinct species within the V. prasinus group. V. kordensis consistently proves to be a sister species to all remaining members of the V. prasinus species group studied by us. Comparatively low genetic distances argue for relatively recent speciation processes within the V. indicus group. The species status of V. caerulivirens and V. finschi is again corroborated. The analyses consistently place V. cerambonensis and V. melinus as sister species. It is further evident that both species groups within Euprepiosaurus still contain distinct unrecognized taxa. Finally, we discuss the phylogeny and zoogeography of Euprepiosaurus in the light of our data and provide an identification key for the species of this subgenus.